Kindled emotions: Commemoration and the importance of meaning making, support and recognition - Huibertha B. Mitima-Verloop; Trudy T. M. Mooren; Paul A. Boelen (PLoS ONE, 2023)
Commemorative events, organized in the aftermath of war or large-scale violence, can have an emotional impact on those who are attending. We examined several characteristics that might influence this impact. In a quasi-experimental pretest-posttest study, participants (n = 307) watched footage of the broadcast of the Dutch National Commemoration, in which World War II is remembered. A control group of 48 participants watched the commemoration broadcast live on Remembrance Day. They were matched for age, gender, war experience and migration background with 48 participants from the study group who watched the footage, to conduct a comparability check. We found some evidence that watching the footage was comparable to watching the commemoration live on Remembrance Day in terms of emotional response and experience of psychosocial factors. Participants in the footage sample (n = 307) responded with an increase of negative and decrease of positive emotions. Individual characteristics were limitedly related to the emotional response; posttraumatic stress symptom severity predicted increased negative emotions. Experiencing meaning making, support and, to a lesser extent, recognition through commemorating was related to experiencing more positive emotions. The findings indicate these psychosocial factors may buffer the emotional distress elicited by commemoration and contribute to important cognitive and social benefits. Practical implications are discussed.